Hormonal therapy is effective and safe for cryptorchidism caused by idiopathic hypogonadotropic hypogonadism in adult males - Sun, Taotao; Xu, Wenchao; Xu, Hao; Chen, Yinwei; Niu, Yonghua; Wang, Daoqi; Wang, Tao; Yang, Weimin; Liu, Jihong (Frontiers in Endocrinology, 2023)
Background: Hormonal therapy is a reasonable treatment for cryptorchidism caused by idiopathic hypogonadotropic hypogonadism (IHH). However, the clinical evidence whether it is effective and safe for the treatment of cryptorchidism caused by IHH is lacking. Aim: To evaluate the effect of hormonal therapy in testicular descent, puberty development and spermatogenesis in adult cryptorchidism males caused by IHH. Methods: This retrospective study included 51 cryptorchidism patients caused by IHH from the Andrology Clinic of University affiliated teaching hospital. Patients were divided into two groups: group A, patients received hormonal therapy; group B, patients received surgical treatment for cryptorchidism followed by hormonal therapy. Results: The rate of successful testicular descent following hormonal therapy (19/32 in group A) or surgical treatment (11/19 in group B) showed no statistically significant difference. There was also no statistically significant difference in penile length, Tanner stage of pubic hair, testicular volume and successful rate of spermatogenesis between the two groups. Testicular atrophy was seen in a single patient in group B. Conclusions: Hormone therapy in adult cryptorchidism males caused by IHH is effective and safe in regards to testicular descent, puberty development and spermatogenesis. This study provides new insight into the treatment of cryptorchidism caused by IHH, highlights that hormonal therapy could be an effective, safe and economic treatment option for cryptorchidism males caused by IHH.